PENGEMBANGAN GRIT KARYAWAN BERBASIS MANAJEMEN TALENTA - Widodo Widodo; Heru Sriyono (JABE (Journal of Applied Business and Economic), 2020)
Every business entity really needs employee grit which is reflected in its persistence and enthusiasm to achieve long-term goals which are demonstrated through hard work in facing challenges, sustaining business and interests for years despite the failure, resilience, and difficulties in achieving it. But in reality the grit of the employees is still relatively limited. One reliable factor for developing grit is talent management. This research was conducted to analyze the employee grit development based talent management grit. The study uses a qualitative approach with descriptive methods. Data obtained through literature review and analyzed descriptive-qualitatively. The results showed that talent management is very necessary to develop employee grit, so companies need to schedule more intense talent management so that employee grit grows optimally.